The Relationship between Scout Activities with the Attitude of State Defend Student’s SMA Negeri 1 Sumberlawang Sragen Academic Year 2018/2019 - Mujiyono Mujiyono; Triana Rejekiningsih; Dewi Gunawati (Budapest International Research and Critics University, 2020)
The purpose of this study is to: 1. Describe the activeness of students in scouting activities, 2. Describe the attitude of the state defends, 3. Explain the relationship between the activities of scouting with the attitude of the state defends. The study was conducted by survey method. The population was all students in class XI. The research sample was taken by a random sampling technique totaling 60 students. The analysis technique is done by product-moment analysis. The results showed that students who actively participated in scout activities were moderate. Likewise, the attitude of defending a student's country is moderate. The results of the analysis obtained an r count of 0.585 with a significance of 0.001 <0.05. The activeness in participating student activities is included in the moderate category, as well as the defensive attitude of students including moderate. The contribution of active participation in scouting activities towards the defense of the state was 34.2%. Then it can be concluded that students who are active in scouting activities have a high state defense attitude compared to students who are not active in these activities.